2022
DOI: 10.1002/jso.26915
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of robot‐assisted nipple‐sparing mastectomy using the da Vinci SP system

Abstract: Background As patients tend to be diagnosed with breast cancer at an early stage, the demand for better cosmetic outcomes has increased. Several studies revealed that robot‐assisted nipple‐sparing mastectomy (RNSM) shows favorable outcomes. The aim of the study was to reveal the feasibility of RNSM using the da Vinci single‐port (SP) system with a minimal incision, hidden in the arm. Methods From 2018 to 2021, 81 cases (70 patients) were retrospectively reviewed. Clinicopathologic characteristics, operative ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…The largest worldwide study using the daVinci SP Robotic Surgical System to perform an rNSM consisted of 81 cases (70 patients) in Asia. Go et al demonstrated Clavien-Dindo Classification Grade III complications in 6 patients with nipple ischemia (2.5%), requiring intervention in 1 patient. The current study included 1 Grade III complication (2.5%) consisting of NAC ischemia requiring debridement, which compares favorably with a large systemic review by Headon et al demonstrating a 5.9% rate of nipple necrosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The largest worldwide study using the daVinci SP Robotic Surgical System to perform an rNSM consisted of 81 cases (70 patients) in Asia. Go et al demonstrated Clavien-Dindo Classification Grade III complications in 6 patients with nipple ischemia (2.5%), requiring intervention in 1 patient. The current study included 1 Grade III complication (2.5%) consisting of NAC ischemia requiring debridement, which compares favorably with a large systemic review by Headon et al demonstrating a 5.9% rate of nipple necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the inherent limitations of a multiarm platform with small working spaces leading to robotic arm collisions, limited ergonomic use of the arms, and limited robotic camera mobility have led to the development of the da Vinci single-port (SP) robotic platform (Intuitive Surgical) with a flexible 3-dimensional camera and robotic arms with increased range of motion limiting collisions. Initial single institution studies using the SP robotic platform in rNSM procedures for high-risk genetic mutations or breast cancer demonstrated feasibility in a small cohort of patients in Asia …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An international multicenter pooled data analysis involving 755 cases of RNSM in 2022 by Park et al 118 further demonstrated its oncologic safety, in terms of events of survival such as local recurrence, regional lymph node recurrence, and distant recurrence, compared with conventional NSM with a median follow-up of 18 months both before ( P =0.28) and after ( P =0.29) propensity-score matching. However, the universal obstacles, such as instrument collision and prolonged docking time, came along with the cumbersome multi-port surgical platform inserted and working in the narrow space during the gradual adoption of SIRAS in mastectomy (Table 4 ) 117 121 . To address these hurdles, Park et al 119 applied the Da Vinci SP system into RNSM with immediate reconstruction in 2018 with the advantage of detailed movement of instrument arms, enhanced vision provided by cobra-like camera, and ergonomic improvement.…”
Section: The Research Status Of Sirasmentioning
confidence: 99%
“…To address these hurdles, Park et al 119 applied the Da Vinci SP system into RNSM with immediate reconstruction in 2018 with the advantage of detailed movement of instrument arms, enhanced vision provided by cobra-like camera, and ergonomic improvement. They furthermore reported 81 cases (70 patients) of RNSM using the SP system between 2018 and 2021 in a retrospective study 121 . Complications requiring intervention occurred in six cases (7.5%) among which occurred one case (2.5%) of nipple-areolar complex necrosis, comparatively lower than multiport RNSM, and no cases of conversion to open mastectomy were reported, indicating its safety and feasibility.…”
Section: The Research Status Of Sirasmentioning
confidence: 99%